Berek & Novak's gynecology. - Berek, Jonathan S.; Novak, Emil, 1883-1957. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
"Berek and Novak's Gynecology is the gold standard text in general gynecology serving both as a comprehensive reference and a practical, clinically-oriented text. This reference is not only a must-have product for residents in training, but it offers information for the practicing physician. The book covers the entire spectrum of women's healthcare by offering guidance for the management of specific gynecologic conditions in eight sections. The first two sections cover principles of practice and initial assessment and the relevant basic science. The third section is on preventive and primary care for women, and the remaining five sections are directed at methods of diagnosis and management in general gynecology, operative general gynecology, urogynecology and pelvic reconstructive surgery, reproductive endocrinology, and gynecologic oncology"--Provided by publisher.
section I. Principles of practice -- section II. Basic principles -- section III. Preventive and primary care -- section IV. General gynecology -- section V. Operative gynecology -- section VI. Urogynecology and pelvic reconstructive surgery -- section VII. Reproductive endocrinology -- section VIII. Gynecologic oncology.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Gynecology; Electronic books